Effect of melting processes on the structure and precipitation of a heavy rainstorm in Beijing - Chunwei Guo; Hui Xiao; Wei Wen; Huiling Yang (Atmospheric Science Letters, 2020)
Abstract Beijing and its surrounding areas experienced a torrential rainstorm from July 21 to 22, 2012. Previous studies have shown that melting was the main rainwater source in this process. In this paper, melting conversion processes were set to zero (NPMLT test) to analyze the effect of microphysical processes on the structure and precipitation of the convective system. The results showed that without the melting processes, the wind shear at the 700 hPa level decreased, and the wind field in Beijing and its surrounding areas changed. The cold front system moved faster, and the rainfall amount only reached the low rain level, much lower than that during the actual rainstorm. The hydrometeors sources had apparently changed. Though the latent heat release was large and little latent heat absorption occurred in the NPMLT test, the net latent heat did not affect the development of the convective system, and the precipitation was low. Therefore, microphysical processes greatly influence precipitation and convective system.